ANALISIS IMPLEMENTASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DALAM PENGELOLAAN KORESPONDENSI DI DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN PATI - Irma Fitria Handayani; Nina Oktarina (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of the Integrated Dynamic Archival Information System (SRIKANDI) in correspondence management at the Pati Regency Archives and Library Office as part of the government’s digital transformation. This study employs a qualitative descriptive approach, utilizing data collection techniques such as observation, interviews, and documentation of informants directly involved in using the system. Data analysis was conducted using thematic analysis techniques, referencing DeLone and McLean’s information system success model, which encompasses system quality, information quality, service quality, usage, user satisfaction, and net benefits. indicate that the implementation of SRIKANDI has improved the efficiency of mail management, accelerated administrative processes, and supported more effective coordination and integration among agencies. Additionally, this system facilitates easier access to information and more structured digital records management. However, several challenges remain in its implementation, such as internet connectivity issues, limited human resource capabilities, and the underutilization of certain system features. Therefore, it is necessary to enhance human resource capacity, strengthen technological infrastructure, and conduct continuous system evaluations to support the optimization of SRIKANDI’s implementation in the future.